2022
DOI: 10.23970/ahrqepccer257
|View full text |Cite
|
Sign up to set email alerts
|

Schedule of Visits and Televisits for Routine Antenatal Care: A Systematic Review

Abstract: Background. The American College of Obstetricians and Gynecologists and the Society for Maternal-Fetal Medicine plan a new evidence-based joint consensus statement to address the preferred visit schedule and the use of televisits for routine antenatal care. This systematic review will support the consensus statement. Methods. We searched PubMed®, Cochrane databases, Embase®, CINAHL®, ClinicalTrials.gov, PsycINFO®, and SocINDEX from inception through February 12, 2022. We included comparative studies from high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…Given the limited conclusions from our prior systematic review of the benefits and harms of reduced care schedules and televisits, 7 the qualitative evidence provides helpful insights into the perspectives, preferences, and experiences of pregnant individuals, their health care professionals, and, in some cases, the clinic leadership with respect to implementing these changes in routine antenatal care. These findings will be important to consider as more research on alternative care schedules and televisits emerges and consensus on these methods of delivery evolves.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited conclusions from our prior systematic review of the benefits and harms of reduced care schedules and televisits, 7 the qualitative evidence provides helpful insights into the perspectives, preferences, and experiences of pregnant individuals, their health care professionals, and, in some cases, the clinic leadership with respect to implementing these changes in routine antenatal care. These findings will be important to consider as more research on alternative care schedules and televisits emerges and consensus on these methods of delivery evolves.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10] Qualitative studies suggest that patients and health care professionals are open to a reduced number of scheduled routine antenatal visits but have concerns about quality of care and patient access. 11,12 However, the actual effect of reducing the number of routine antenatal visits has not been adequately summarized.…”
Section: Discussionmentioning
confidence: 99%
“…This article is based on an AHRQ Comparative Effectiveness Review, which also addressed incorporation of televisits into routine antenatal care and qualitative research on routine antenatal schedules and televisits. 11,14…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 19, 2023. ; https://doi.org/10.1101/2023.04.17.23288705 doi: medRxiv preprint noted inconsistencies in which outcomes are routinely collected and reported [6][7][8][9]. There is a need for consistent reporting of maternal and infant outcomes in future clinical trials that compare the traditional 12 to 14 in-office visit approach with new models of prenatal care schedules that incorporate different frequency of visits and use of telemedicine.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Two systematic reviews were recently commissioned for evaluating the effect of varying the frequency of prenatal care visit schedule recommendations on maternal and infant outcomes [5,9]. To identify any additional outcome measures published in the literature, we will supplement these systematic reviews with an electronic investigation with no date or language boundary using the databases of MEDLINE via the PubMed interface, Web of Science, Embase (Excerpta Medica Database), and CENTRAL (Cochrane Central Register of Controlled Trials) to identify outcome measures in systematic reviews that reported on the effect of different frequency of prenatal visit recommendations on maternal and infant outcomes.…”
Section: Phase One: Developing a Preliminary Core Measurement Outcome...mentioning
confidence: 99%